From Farmers to World: Local Coffee Go to Global Stage - Usman, Berto; Misliniyati, Rena; Fiona, Febzi; Aprisella, Rhienta (PT. Riset Press International, 2025)
This Community Service Program conducted in Talang Babatan Village, Kepahiang District, Bengkulu, aims to empower the local community through the enhancement of human resources in coffee production. The project focuses on developing Talang Babatan as a competitive and sustainable coffee-producing village. Despite its potential, the community faces challenges including limited knowledge of modern coffee processing, weak production management, and inadequate access to broader markets. Activities conducted include field visits, community discussions, problem identification, and training sessions focused on improving the knowledge and skills of coffee farmers in post-harvest processing, diversification, and product branding. Preliminary outcomes indicate improved awareness and readiness among local farmers and women’s groups to adopt innovative methods in coffee processing and marketing. Through these initiatives, the program contributes to enhancing the village’s economic resilience and positioning local coffee on the global stage.